Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1159/000366359
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of RIG-I in Oral Keratinocytes and Fibroblasts

Abstract: Background: Innate immune response by oral mucosal cells may be the first line of host defense against viral infection. Retinoic acid-inducible gene-I (RIG-I) recognizes viral dsRNA in the cytoplasm, and RIG-I-mediated signaling regulates antiviral type I IFN, and inflammatory chemokine production. Here, we tested the hypothesis that oral mucosal cell participation in host defense against viral infection via RIG-I. Methods: RIG-I expression was detected in immortalized oral keratinocytes (RT7), oral fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
(39 reference statements)
0
28
0
Order By: Relevance
“…Keratinocytes of the RT7 immortalized human oral keratinocyte cell line were established by transfection of human telomerase reverse transcriptase and E7, as previously described (60), and were then cultured in keratinocyte growth medium (KGM) supplemented with human epidermal growth factor, insulin, hydrocortisone, calcium, bovine pituitary extract, gentamicin sulfate, and amphotericin B (Lonza, Walkersville, MD). We also prepared primary cultures of human oral keratinocytes obtained from healthy gingival tissues excised during extraction of impacted teeth from 3 different patients, as previously reported (61). Informed consent for acquisition of those tissues was obtained according to a protocol approved by the Ethical Committee of Hiroshima University.…”
Section: Methodsmentioning
confidence: 99%
“…Keratinocytes of the RT7 immortalized human oral keratinocyte cell line were established by transfection of human telomerase reverse transcriptase and E7, as previously described (60), and were then cultured in keratinocyte growth medium (KGM) supplemented with human epidermal growth factor, insulin, hydrocortisone, calcium, bovine pituitary extract, gentamicin sulfate, and amphotericin B (Lonza, Walkersville, MD). We also prepared primary cultures of human oral keratinocytes obtained from healthy gingival tissues excised during extraction of impacted teeth from 3 different patients, as previously reported (61). Informed consent for acquisition of those tissues was obtained according to a protocol approved by the Ethical Committee of Hiroshima University.…”
Section: Methodsmentioning
confidence: 99%
“…RIG‐I‐like receptors (RLR) are cytoplasmic RNA helicases, which are expressed at low levels in resting cells, but their expression is strongly induced during viral infection by secretion of type I interferons as well as proinflammatory cytokines including IFN‐γ, IL‐1β and TNF . It has been demonstrated that RIG‐I is constitutively expressed in cells of the connective tissue including fibroblasts, epithelial and endothelial cells . Moreover, it has been shown that RIG‐I‐deficient MEF failed to generate IFN‐β upon viral infection, while virus‐infected dendritic cells from RIG‐I −/− mice secrete large amounts of type I IFN , indicating that RIG‐I plays an important role in non‐professional immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reveal that the RLR play an important role in the antiviral response of non‐professional immune cells, including fibroblasts, keratinocytes, endothelial cells and epithelial cells . While resting cells show relatively low levels of RLR, their expression is strongly induced after viral infection and exposure to type I interferons (IFN) .…”
Section: Introductionmentioning
confidence: 99%
“…Expression levels of receptor-related genes (TLRs [14], NLRs [15,16], and RLRs [17]), which recognize bacterial components, and glyceraldehyde-3-phosphate dehydrogenase (GAPDH as…”
Section: Quantitative Rt-pcr (Rt-qpcr)mentioning
confidence: 99%